First Depressed, Then Discriminated Against? - Stijn Baert; Sarah De Visschere; Koen Schoors; Eddy Omey (Institute for the Study of Labor (IZA), 2014)
This study assesses hiring discrimination based on disclosed depression. We send out pairs of job applications from fictitious unemployed candidates to real vacancies in Belgium. Within each pair, one candidate cites depression as the reason for her/his unemployment, whereas the other candidate reveals no reason for unemployment. Overall, the hypothesis that applicants disclosing former depression are treated unfavourably is rejected. However, if we break up the data by the gender of the recruiter, we see that revealing former depression as a reason for unemployment is rewarded by female recruiters, whereas it affects the hiring decisions made by male recruiters in a non-positive way.
Keywords: I14; J71; C93; 330; economics of health; depression; hiring discrimination; field experiments